The Influence of the Prolactins on the Development of the Uterus in Neonatal Mice - Kang, Jinwen; Liu, Yingnan; Zhang, Yu; Yan, Wankun; Wu, Yao; Su, Renwei (Frontiers in Veterinary Science, 2022)
The endometrial gland is one of the most important components of the mammalian uterus. The secretions of endometrial glands are critical to the successful establishment of pregnancy. However, few studies have been conducted on the regulatory mechanisms of adenogenesis during the development of endometrium. Prolactin is proved to play a role in gland development in ewe. However, the rodents express multiple Prolactin-like genes in addition to the Prolactin gene, named the prolactin family together, which leads to more complexity to studies on the roles of these genes during adenogenesis. In the present study, we detected the genes expression of 35 different prolactin family members (PRLs) together with the prolactin receptor (PRL-R) in the endometrium of neonatal mice along with the adenogenesis process, to address which prolactin-like genes play a key role during gland development in mice. We found that: (1) The expression of Prl1a1, Prl3d1, Prl5a1, Prl7a1, Prl7a2, Prl7d1, Prl8a6, Prl8a8, and Prl8a9 genes were significantly increased along with the development of uterine glands. Prl7c1 and Prl8a1 were observably up-regulated on PND5 when the uterine glandular bud invagination begins. Prl3a1, Prl3b1, and Prl7b1 suddenly increased significantly on PND9. But, Prl3c1 and Prl8a2 were markedly down-regulated on PND5 and the expression of Prl6a1 and Prlr were stable extremely. (2) After continuous injection of Progesterone (P4), a well-known method to suppress the endometrial adenogenesis, the expression of Prl1a1, Prl3d1, Prl5a1, Prl7a1, Prl7a2, Prl7d1, Prl8a6, Prl8a8, Prl8a9, and Prlr were suppressed on PND7. And on PND9, Prl1a1, Prl3d1, Prl8a6, Prl8a8, and Prl8a9 were significantly inhibited. (3) Further analysis of the epithelial and stroma showed that these PRLs were mainly expressed in the endometrial stroma of neonatal mice. Our results indicate that multiple PRLs are involved in uterine development and endometrial adenogenesis. Continued progesterone therapy may alter the expression pattern of these PRLs in endometrial stromal cells, thereby altering the interaction and communication between stroma and epithelium, and ultimately leading to complete suppression of endometrial adenogenesis.